Mixed Randomized Response Model Kim and Warde: Application to students FCM - UNMSM - Matos Zarsoza, José (2016)
This research deals with the behavior of students against sensitive questions at the Faculty of Mathematical Sciences using the Mixed Randomized Response Model proposed by Kim and Warde (2005), which it was applied in a survey conducted at the Faculty of Mathematical Sciences (FCM), to investigate the behavior of young students regarding poor academic practices, make copies, and drug use to improve academic performance in an examination. The study population includes students enrolled in Semester 2015-I belonging to the four professional schools of the Faculty of Mathematical Sciences of San Marcos. Stratified random sampling with proportional allocation to size of each stratum (Schea˙er, Mendenhall, Ott, 2007) was used in the sample design, considering as strata to each of the Professional Schools (EP) of the FCM. For to calculation of sample size is considered a limit to the estimation error of 5% with a confidence level of 95% and information provided by the Academic Board of the FCM, of the students enrolled the first half of the year academic 2015, the sample size was 300 students, distributed proportion to the four EP of the FCM.